Towards a better understanding of the impact of the sequelae of TBI on the social participation of seniors - Marie-Josée Levert; Hélène Lefebvre; Mélanie Levasseur; Isabelle Gélinas; Michelle McKerall; Odette Roy; Michelle Proulx (Archives of Nursing Practice and Care - Peertechz Publications, 2017)
Background: The multiple sequelae caused by traumatic brain injuries (TBIs) can considerably reduce the ability of seniors to resume their activities of daily living and their leisure activities, and to return to meaningful relationships so they can participate in the life of their community. Purpose of the study: This article aims to put forward the perceptions of older participants about the sequelae they themselves identify as consecutive, short or medium long term, with their TBI and consequently, the limitations they experienced in terms of their social participation. Results: The fi ndings reveal a correspondence between the multiple sequelae of the TBI identified by the participants and those documented in the scientifi c writings. These sequelae could be grouped  according to the limitations found in the operational framework's three spheres of activities related to social participation: those that promotes self-realization through an autonomous and independent everyday life; through pastimes and leisure activities; and through relationships with others. Main findings: The findings are innovative compared with what is generally described in the scientific literature, since existing studies offer few concrete examples of the limitations encountered in terms of social participation due to sequelae following a TBI. Four sequelae namely memory loss, loss of balance, lack of motivation or apathy and fatigue, appear to have many impacts on a variety of activities which could explain their signifi cance for participants. Conclusion: The findings pave the way for new research avenues that focus on analyzing social participation opportunities of older adults by reinforcing their capacities. Potential implications: Results provide benchmark for health care and social services professionals for the mobilization of most effective resources and services to help seniors to engage in rewarding, meaningful social participation activities.